Natural variation in the promoter of GsERD15B affects salt tolerance in soybean. Issue 6 (19th January 2021) - Jin, Ting; Sun, Yangyang; Shan, Zhong; He, Jianbo; Wang, Ning; Gai, Junyi; Li, Yan
Summary: Salt stress has detrimental effects on crop growth and yield, and the area of salt‐affected land is increasing. Soybean is a major source of vegetable protein, oil and feed, but considered as a salt‐sensitive crop. Cultivated soybean ( Glycine max ) is domesticated from wild soybean ( G. soja ) but lost considerable amount of genetic diversity during the artificial selection. Therefore, it is important to exploit the gene pool of wild soybean. In this study, we identified 34 salt‐tolerant accessions from wild soybean germplasm and found that a 7‐bp insertion/deletion (InDel) in the promoter of GsERD15B (early responsive to dehydration 15B) significantly affects the salt tolerance of soybean. GsERD15B encodes a protein with transcriptional activation function and contains a PAM2 domain to mediate its interaction with poly(A)‐binding (PAB) proteins. The 7‐bp deletion in GsERD15B promoter enhanced the salt tolerance of soybean, with increased up‐regulation of GsERD15B, two GmPAB genes, the known stress‐related genes including GmABI1, GmABI2, GmbZIP1, GmP5CS, GmCAT4, GmPIP1:6, GmMYB84 and GmSOS1 in response to salt stress. We propose that natural variation in GsERD15B promoter affects soybean salt tolerance, and overexpression of GsERD15B enhanced salt tolerance probably by increasing the expression levels of genes related to ABA‐signalling, proline content, catalase peroxidase, dehydration response and cation transport.